Constant fluctuating asymmetry but not directional asymmetry along the geographic distribution of Drosophila antonietae (Diptera, Drosophilidae) - Costa, Marcelo; Mateus, Rogério P.; Moura, Mauricio O. (Revista Brasileira de Entomologia, 2015)
The population dynamics of a species tends to change from the core to the periphery of its distribution. Therefore, one could expect peripheral populations to be subject to a higher level of stress than more central populations (the center–periphery hypothesis) and consequently should present a higher level of fluctuating asymmetry. To test these predictions we study asymmetry in wing shape of five populations of Drosophila antonietae collected throughout the distribution of the species using fluctuating asymmetry as a proxy for developmental instability. More specifically, we addressed the following questions: (1) what types of asymmetry occur in populations of D. antonietae? (2) Does the level of fluctuating asymmetry vary among populations? (3) Does peripheral populations have a higher fluctuating asymmetry level than central populations? We used 12 anatomical landmarks to quantify patterns of asymmetry in wing shape in five populations of D. antonietae within the framework of geometric morphometrics. Net asymmetry – a composite measure of directional asymmetry+fluctuating asymmetry – varied significantly among populations. However, once net asymmetry of each population is decomposed into directional asymmetry and fluctuating asymmetry, most of the variation in asymmetry was explained by directional asymmetry alone, suggesting that populations of D. antonietae have the same magnitude of fluctuating asymmetry throughout the geographical distribution of the species. We hypothesize that larval development in rotting cladodes might play an important role in explaining our results. In addition, our study underscores the importance of understanding the interplay between the biology of a species and its geographical patterns of asymmetry.